Studi desain Taman Tebet sebagai youth park - Putra, Aprianto Dwi; Kohdrata, Naniek; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap; Vol.4, No.2, Oktober 2018, 2018)
Design study of Taman Tebet as youth park. Jakarta’s green open spaces should have functional value to fulfill the need of heterogeneous people of Jakarta for open public spaces. The absence of character in most of Jakarta’s city parks is underpinning this research. This research’s objective is to illustrate the character of Jakarta’s city park by creating a design concept that fit with current Jakarta’s people needs. The research methods are inventory, analysis, synthesis, concept to design stage. The result of this research is a concept of design that can depict Jakarta city park character today, by applying contemporary landscape elements. The existing design concept will be complemented with design development to strengthen the characteristic of the park. The end products of this research are the design concept, concept of space, concept of circulation, the green layout concept, site plan, and transformation of certain object shape which will be specially displayed. As a conclusion, Youth Park design concept is able to bring a new characters in the park of Jakarta in general and can meet the needs of public space Jakarta now.